2019
DOI: 10.1002/pds.4868
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to ESC guideline‐recommended medications over a 36‐month follow‐up period after hospitalization for heart failure: Results from the EPICAL2 cohort study

Abstract: Purpose The purpose of the study is to describe the trajectories of oral medication prescriptions in patients with heart failure with reduced ejection fraction (HFrEF) over 3 years after discharge from hospitalization for heart failure. We then evaluated the adherence of these prescriptions to the European Society of Cardiology (ESC) guideline‐recommended medications and identified patient characteristics associated with nonadherence. Methods We used data from the EPICAL2 cohort study. HFrEF patients who had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…6,[13][14][15][16][17][18] Almost all adherence studies limited their observation period to around 1 year, 19 but a recent European study has shown that around 64% of patients with HF with reduced ejection fraction remained adherent to dual therapy (RASI and b-blocker) over a 3-year period after hospital discharge. 20 However, little is known about the long-term adherence to EBMs among Australian patients with hospitalized HF, which predominantly affects older patients with a high comorbidity burden that may impact adherence. 21,22 An understanding of the longterm adherence to EBMs and their clinical predictors in a "real-world" population-based HF cohort is necessary to inform targets and potential need for strategies to improve adherence and expected HF outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…6,[13][14][15][16][17][18] Almost all adherence studies limited their observation period to around 1 year, 19 but a recent European study has shown that around 64% of patients with HF with reduced ejection fraction remained adherent to dual therapy (RASI and b-blocker) over a 3-year period after hospital discharge. 20 However, little is known about the long-term adherence to EBMs among Australian patients with hospitalized HF, which predominantly affects older patients with a high comorbidity burden that may impact adherence. 21,22 An understanding of the longterm adherence to EBMs and their clinical predictors in a "real-world" population-based HF cohort is necessary to inform targets and potential need for strategies to improve adherence and expected HF outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Poor drug adherence or non‐persistence in patients with HF have in several studies demonstrated increased morbidity and mortality, as well as increased healthcare costs. 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Poor drug adherence or non-persistence in patients with HF have in several studies demonstrated increased morbidity and mortality, as well as increased healthcare costs. [5][6][7][8] Studies on drug adherence and persistence are important for patients, caregivers, and decision makers to understand targets for implementation of guideline-directed medical therapy (GDMT). Interventions that improve adherence and persistence might have higher impact on HF outcomes than new drugs in the real-world setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ACEI/ARB use is crucial for HFrEF patients, the underutilization of these medications is commonly seen in clinical practice. Bertero et al[27] has reported common factors associated with the nonprescription of ACEI/ARB including higher serum creatinine level, lower systolic blood pressure, and old age. Medication dose reduction is needed in advanced chronic kidney disease.…”
mentioning
confidence: 99%